Treatment Optimization for Hepatocellular Carcinoma in Elderly Patients in a Japanese Nationwide Cohort. Issue 1 (July 2019) - Kaibori, Masaki; Yoshii, Kengo; Hasegawa, Kiyoshi; Ogawa, Asao; Kubo, Shoji; Tateishi, Ryosuke; Izumi, Namiki; Kadoya, Masumi; Kudo, Masatoshi; Kumada, Takashi; Sakamoto, Michiie; Nakashima, Osamu; et al.
Abstract : Objective: We reviewed nationwide follow-up data to determine outcomes of different treatments for early-stage hepatocellular carcinoma (HCC) in elderly patients. Summary Background Data: Outcomes of early-stage HCC treatments in elderly patients have not been prospectively compared. Methods: We included 6490 HCC patients, aged ≥75 years at treatment, who underwent curative hepatic resection (HR, n = 2020), radiofrequency ablation (RFA, n = 1888), microwave ablation (MWA, n = 193), or transcatheter arterial chemoembolization (TACE, n = 2389), and compared their characteristics and survival. We used matching propensity score analysis (PSA) between the HR and RFA subgroups with tumors ⩽3 cm to overcome baseline bias. Results: The HR group had significantly longer recurrence-free survival (RFS) than the RFA, MWA, and TACE groups [RFA vs HR—hazard ratio: 1.22, 95% confidence interval (CI): 1.09–1.37, P < 0.001; MWA vs HR—hazard ratio: 1.51, 95% CI: 1.22–1.88, P < 0.001; TACE vs HR—hazard ratio: 2.70, 95% CI: 2.44–2.99, P < 0.001). HR and RFA patients had significantly longer overall survival (OS) than the TACE group (RFA vs HR—hazard ratio: 1.01, 95% CI: 0.87–1.17, P = 0.919, TACE vs HR—hazard ratio: 2.11, 95% CI: 1.86–2.40, P < 0.001). PSA successfully matched HR and RFA patients from with primary HCC tumors ⩽3.0 cm and similar liver function and tumor characteristics; and showed significantly longer RFS (hazard ratio: 1.64, 95% CI: 1.29–2.10, P < 0.001) and OS (hazard ratio: 1.57, 95% CI: 1.12–2.20, P = 0.009) for HR than for RFA (including subgroup analyses). In Cox proportional hazard analysis, HR offered better prognosis than RFA. Conclusions: HR decreases recurrence risk and improves OS in patients aged ≥75 years with primary HCC tumors ⩽3.0 cm. Abstract : Supplemental Digital Content is available in the text